An Alternative Approximation to the Variance of Transformation Score - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 1999)
Provides an alternative approximation to the variance of transformation score, based on an asymptotic expansion of the transformation estimator. Comparison with variance approximation in terms of standardized scores; Monte Carlo simulations.